Prevalence of serologic markers for hepatitis B and C viruses in Brazilian blood donors and incidence and residual risk of transfusion transmission of hepatitis C virus. Issue 4 (6th August 2012) - de Almeida‐Neto, Cesar; Sabino, Ester Cerdeira; Liu, Jing; Blatyta, Paula Fraiman; Mendrone‐Junior, Alfredo; Salles, Nanci Alves; Leão, Silvana Carneiro; Wright, David J.; Basques, Fernando Valadares; Ferreira, João Eduardo; Busch, Michael P.; Murphy, Edward L.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND: We evaluate the current prevalence of serologic markers for hepatitis B virus (HBV) and hepatitis C virus (HCV) in blood donors and estimated HCV incidence and residual transfusion‐transmitted risk at three large Brazilian blood centers. STUDY DESIGN AND METHODS: Data on whole blood and platelet donations were collected from January through December 2007, analyzed by center; donor type; age; sex; donation status; and serologic results for hepatitis B surface antigen (HBsAg), antibody to hepatitis B core antigen (anti‐HBc), and anti‐HCV. HBV and HCV prevalence rates were calculated for all first‐time donations. HCV incidence was derived including interdonation intervals that preceded first repeat donations given during the study, and HCV residual risk was estimated for transfusions derived from repeat donors. RESULTS: There were 307, 354 donations in 2007. Overall prevalence of concordant HBsAg and anti‐HBc reactivity was 289 per 100, 000 donations and of anti‐HCV confirmed reactivity 191 per 100, 000 donations. There were significant associations between older age and hepatitis markers, especially for HCV. HCV incidence was 3.11 (95% confidence interval, 0.77‐7.03) per 100, 000 person‐years, and residual risk of HCV window‐phase infections was estimated at 5.0 per million units transfused. CONCLUSION: Improvement in donor selection, socioeconomic conditions, and preventive measures, implemented over time, may have helped to decrease prevalence of HBV and HCV, relative to previous reports. Incidence and residual risk of HCV are also diminishing. Ongoing monitoring of HBV and HCV markers among Brazilian blood donors should help guide improved recruitment procedures, donor selection, laboratory screening, and counseling strategies.